Differential eq (implicit sol)

  • Thread starter Qyzren
  • Start date
  • #1
44
0

Homework Statement


i have a differential equation.

∂h/∂t + [g sin a h²/v]∂h/∂x = 0. where h = h(x,t).
i need to show by substitution that the (implicit) general solution for h is h = f(x - (g sin a h²t/v)) where f is an arbitrary differential function of a single variable.


The Attempt at a Solution


∂h/∂x = ∂f/∂x
∂h/∂t = ∂f/∂t * (-g sin a h²/v)
subbing in gives
∂f/∂t*(-g sin a h²/v) + (g sin a h²/v)*∂f/∂x = 0
cancelling g sin a h²/v
-∂f/∂t + ∂f/∂x = 0
so now i have to show... ∂f/∂t = ∂f/∂x ???
seems like i'm going in circles...

any help will be appreciated
 

Answers and Replies

  • #2
179
4
try:

h(x,t)=f(y(x,t))
 
  • #3
152
0
I'm not sure where the brackets should be, so let me just confirm that this is the problem:

[tex]\frac{\partial h}{\partial t} + \frac{gsin(a)h^2}{v}\frac{\partial h}{\partial x} = 0[/tex]

[tex] h=f(x-\frac{gsin(a)h^{2}t}{v})[/tex]
 
  • #4
152
0
Okay I worked through it, that must be the correct form. Your problem is that you're interpreting f as a function of two variables. As xaos said, write h=f(y(x,t)). Then:

[tex] \frac{\partial h}{\partial t} = f'(y)\frac{\partial}{\partial t}(y) [/tex]
 
  • #5
HallsofIvy
Science Advisor
Homework Helper
41,847
966

Homework Statement


i have a differential equation.

∂h/∂t + [g sin a h²/v]∂h/∂x = 0. where h = h(x,t).
i need to show by substitution that the (implicit) general solution for h is h = f(x - (g sin a h²t/v)) where f is an arbitrary differential function of a single variable.


The Attempt at a Solution


∂h/∂x = ∂f/∂x
∂h/∂t = ∂f/∂t * (-g sin a h²/v)
f is a function of a single variable so "[itex]\partial f/\partial x[/itex]" and "[itex]\partial f/\partial t[/itex]" are meaningless. Having that "h" inside f makes it complicated: More correctly
[tex]\partial h/\partial x= f'(x- (g sin(ah^2t/v))(1- 2aght/v)(-g cos(ah^2t/v))(2aht/v)\partial h/\partial x[/tex]
and
[tex]\partial h/\partial t= f'(x- (g sin(ah^2t/v)(-2aght/v)(-gcos(ah^2t/v))((2aht/v)\partial h/\partial t+ ah^2/v)[/tex]

subbing in gives
∂f/∂t*(-g sin a h²/v) + (g sin a h²/v)*∂f/∂x = 0
cancelling g sin a h²/v
-∂f/∂t + ∂f/∂x = 0
so now i have to show... ∂f/∂t = ∂f/∂x ???
seems like i'm going in circles...

any help will be appreciated
 

Related Threads on Differential eq (implicit sol)

Replies
5
Views
1K
Replies
1
Views
2K
Replies
4
Views
5K
  • Last Post
Replies
5
Views
667
  • Last Post
Replies
2
Views
1K
  • Last Post
Replies
3
Views
3K
  • Last Post
Replies
5
Views
341
Replies
5
Views
1K
  • Last Post
Replies
1
Views
1K
Top